Delayed laparoscopic cholecystectomy increases the total hospital stay compared to an early laparoscopic cholecystectomy after acute cholecystitis: an updated meta analysis of randomized controlled trials. Issue 10 (October 2015) - Menahem, Benjamin; Mulliri, Andrea; Fohlen, Audrey; Guittet, Lydia; Alves, Arnaud; Lubrano, Jean
Abstract: Background: The objective of this study was to review the available prospective, randomized, controlled trials to determine whether an early (ELC) or a delayed (DLC) approach to a laparoscopic cholecystectomy is associated with an increase in length of hospitalization after acute cholecystitis. Methods: Medline, the Cochrane Trials Register and EMBASE were searched for prospective, randomized, controlled trials (RCTs) comparing ELC versus DLC, published up to May 2014. A meta analysis was performed using Review Manager 5.0. Results: Nine RCTs were included in a total of 617 who underwent ELC and 603 patients who underwent DLC after acute cholecystitis. The mean hospital stay was 5.4 days in the ELC group and 9.1 days in the DLC group. The meta analysis showed a mean hospital stay significantly lower in the ELC group [medical doctor (MD) = 3.24, 95% confidence interval (CI) = 1.95–4.54, P < 0.001]. The major biliary duct injury rate in the ELC group was 0.8% (2/247) and 0.9% (2/223) in the DLC group. The meta analysis showed no significant difference between the ELC and DLC groups [relative risk (RR) =0.96, 95%CI = 0.25–3.73, P  = 0.950]. Conclusion: DLC is associated with a longer total hospital stay but equivalent morbidity as compared to ELC for patients presenting with acute cholecystitis. ELC would appear to be the treatment of choice for patients presenting with ELC.